2023
DOI: 10.1021/acs.cgd.3c00311
|View full text |Cite
|
Sign up to set email alerts
|

Case of Chiral Resolution through Converting Two Racemic Compounds into a Conglomerate

Abstract: The formation of a conglomerate is always attractive, which is a prerequisite for chiral resolution by a flexible and productive preferential crystallization. This present study is aimed at exploring the possibility of chiral resolution in a two racemic compound system. The racemic conglomerate of S–S and R–R was prepared by slurring RS-naproxen (RS-NAP) with RS-1-(2-naphthyl) ethylamine (RS-NEA), which was determined by powder X-ray diffraction, differential scanning calorimetry, single-crystal X-ray diffract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Cocrystal-based techniques, such as cocrystal-PE, 194,198 CBRderacemization, 239 and CBR-PC, [243][244][245] represent promising candidates for exploring enantioseparation mechanisms, expanding the substrate scope and enabling the efficient "reciprocal resolution" of complicated enantiomers. Hence, it will be a trendsetting topic to explore the mechanism of enan-tiospecic cocrystal formation using crystal structures and DFT calculations including the binding energy, crystal packing mode, and solvation free energy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cocrystal-based techniques, such as cocrystal-PE, 194,198 CBRderacemization, 239 and CBR-PC, [243][244][245] represent promising candidates for exploring enantioseparation mechanisms, expanding the substrate scope and enabling the efficient "reciprocal resolution" of complicated enantiomers. Hence, it will be a trendsetting topic to explore the mechanism of enan-tiospecic cocrystal formation using crystal structures and DFT calculations including the binding energy, crystal packing mode, and solvation free energy.…”
Section: Discussionmentioning
confidence: 99%
“…12n ). 245 Hence, previously reported chiral cocrystals, in particular those possessing higher thermodynamic stability than their pristine racemates, may provide upgraded versions for developing more cases of “reciprocal resolution”.…”
Section: Crystallization-based Methods For Chiral Separationmentioning
confidence: 99%
“…23 Going beyond the use of achiral coformers, Zhou et al 25 successfully combined two racemic compounds to form a conglomerate (Scheme 1, eqn (7)), hereby enabling the two compounds to be resolved simultaneously by preferential crystallization. 25–27 These authors, later showed that the combination of two racemic compounds, however, rarely leads to conglomerate formation, with an overall racemic compound (containing both racemates, Scheme 1, eqn (6)) more likely to form. 28 Scheme 1 summarizes potential cocrystallization outcomes between a racemic target and an achiral, enantiopure, or racemic resolving agent.…”
mentioning
confidence: 99%